Inhibitory Effects of Quercetin and Its Human and Microbial Metabolites on Xanthine Oxidase Enzyme - Mohos, Violetta; Pánovics, Attila; Fliszár-Nyúl, Eszter; Schilli, Gabriella; Hetényi, Csaba; Mladěnka, Přemysl; Needs, Paul W; Kroon, Paul A; Pethő, Gábor; Poór, Miklós (International journal of molecular sciences, 2019)
Quercetin is an abundant flavonoid in nature and is used in several dietary supplements. Although quercetin is extensively metabolized by human enzymes and the colonic microflora, we have only few data regarding the pharmacokinetic interactions of its metabolites. Therefore, we investigated the interaction of human and microbial metabolites of quercetin with the xanthine oxidase enzyme. Inhibitory effects of five conjugates and 23 microbial metabolites were examined with 6-mercaptopurine and xanthine substrates (both at 5 μM), employing allopurinol as a positive control. Quercetin-3'-sulfate, isorhamnetin, tamarixetin, and pyrogallol proved to be strong inhibitors of xanthine oxidase. Sulfate and methyl conjugates were similarly strong inhibitors of both 6-mercaptopurine and xanthine oxidations (IC50 = 0.2-0.7 μM); however, pyrogallol inhibited xanthine oxidation (IC50 = 1.8 μM) with higher potency vs. 6-MP oxidation (IC50 = 10.1 μM). Sulfate and methyl conjugates were approximately ten-fold stronger inhibitors (IC50 = 0.2-0.6 μM) of 6-mercaptopurine oxidation than allopurinol (IC50 = 7.0 μM), and induced more potent inhibition compared to quercetin (IC50 = 1.4 μM). These observations highlight that some quercetin metabolites can exert similar or even a stronger inhibitory effect on xanthine oxidase than the parent compound, which may lead to the development of quercetin-drug interactions (e.g., with 6-mercaptopurin or azathioprine).
Keywords: Protein Binding; xanthin; Quercetin; xanthinoxidasa; Structure-Activity Relationship; molekulární struktura; Molecular Structure; vztah mezi dávkou a účinkem léčiva; Enzyme Inhibitors; Xanthine Oxidase; molekulární modely; molekulární konformace; vztahy mezi strukturou a aktivitou; Xanthine; oxidace-redukce; Models, Molecular; vazba proteinů; lidé; Humans; alopurinol; Catalysis; Molecular Conformation; Oxidation-Reduction; Dose-Response Relationship, Drug; inhibitory enzymů; katalýza; quercetin; Allopurinol